Towards Secure Encryption in Cloud Environment - Neha (My University, 2018)
In the advent of information technology, the dramatic rise of computational and storage limits alongside the improvement of overall correspondences guarantee exceptionally customized, very much planned and advantageous administrations. In the cloud storage condition, it ends up being particularly real in light of the way that the data is arranged in different spots. Data security and privacy assurance are the two essential standards of customer's worry. Numerous strategies in cloud storage have been researched in academics as well as enterprises. Information security and protection assurance are winding up more vital for the fate of developing cloud technology. So, this dissertation work concentrates on the security of data in information systems. Homomorphic cryptography is a possible and promising nominee for this reason. This innovation permits controlling encoded information and performing consistent operations on it without really getting to the decoded data. This study presents implementation of Advanced Encryption Standard algorithm and proposed technique giving a concise view on how the encoding/decoding of both techniques works for the file encryption and decryption. And examines how homomorphic cryptography can empower security, by first giving a profound understanding of the field of protection in computer science.
Keywords: Cryptography; cloud; data security; homomorphic encryption